2015
DOI: 10.1111/cei.12668
|View full text |Cite
|
Sign up to set email alerts
|

IL-1R1 is expressed on both Helios+ and Helios−FoxP3+CD4+ T cells in the rheumatic joint

Abstract: SummarySynovial fluid from rheumatic joints displays a well-documented enrichment of forkhead box protein 3 (FoxP3)1 regulatory T cells (tissue We also demonstrate a striking enrichment of IL-1R1 expression in synovial CD4 1 T cells that was restricted to the CD25-expressing FoxP3 population, but independent of Helios. IL-1R1 expression appears to define a tissue T reg cell phenotype together with the expression of CD25, glucocorticoid-induced TNF receptor family-related gene (GITR) and CTLA-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Previous studies have showed that Helios - but not Helios + human FOXP3 Tregs produce a variety of cytokines ex vivo , including the anti-inflammatory cytokine IL-10 ( 39 , 40 ). Therefore, we next examined the ability of human AdipoR1 + and AdipoR1 - Treg subsets to produce IL-10.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have showed that Helios - but not Helios + human FOXP3 Tregs produce a variety of cytokines ex vivo , including the anti-inflammatory cytokine IL-10 ( 39 , 40 ). Therefore, we next examined the ability of human AdipoR1 + and AdipoR1 - Treg subsets to produce IL-10.…”
Section: Resultsmentioning
confidence: 99%
“…Since IL-1R family members signal through MyD88 (34), MFYcre T regs must lack the ability to signal through cytokines such as IL-1b and IL-33 produced by APC and other cells in the milieu. These cytokines have been previously shown to impact mucosal and tissue T regs (35,36). Therefore, we tested the effects of IL-1b and IL-33 on T reg proliferation.…”
Section: Loss Of Myd88 In Foxp3 + Cells Reduces T Reg Accumulation Inmentioning
confidence: 99%
“…In addition, both IL-1R1 and IL-1R2 are induced on human Tregs after TCR signaling [ 281 ]. Moreover, in the context of rheumatoid arthritis, IL-1R1 is expressed on tissue-activated Tregs [ 282 ]. Recently, in mice, Th17 polarizing conditions have been shown to favor IL-1R1 expression by Tregs.…”
Section: Treg Stabilizationmentioning
confidence: 99%